Risk management in Bank Islam / Qurratul Aini Abu Hanifah - Abu Hanifah, Qurratul Aini (Academy of Contemporary Islamic Studies (ACIS), 2016)
This paper seeks to understand risk management in Bank Islam and risk analysis that lead to the failure of that. Risk management is an activity which integrates recognition of risk, risk assessment, developing strategies to manage it, and mitigation of risk using managerial resources. Some traditional risk managements are focused on risks stemming from physical or legal causes (e.g. natural disasters or fires, accidents, death). Financial risk is essentially a capital operation risks. For the modern enterprise, working capital in business activities is to support the operation of their overall funding, and is the foundation of sustainable management and health development. In this paper, the financial risks of business activities of modern enterprises is studied, the risk forms of expression in business activities and the objective and subjective reasons of them are discussed. On this basis, a modern enterprise risk management system is constructed, and methods and strategies of risk management are proposed, for enterprises to choose reference.